Relationship between leaders' emotional intelligence, organisational commitment, job satisfaction, and turnover intention in Jordanian hotel industry - Al-Zgool, Mahmoud Radwan Hussein (2015)
The employees’ turnover phenomenon in the hotel industry is being focused upon by managers and academicians because employees’ attitudes and behaviours play a vital role in developing hotels. Meanwhile, this phenomenon is linked to employees’ job satisfaction (JS) and their organisational commitment (OC). Therefore, to manage employees’ turnover, the management must reduce the intention of turnover amongst employees. Given the phenomenal growth of the Jordanian hotels over the last ten years, it is important for leaders to understand, predict and control employees’ turnover intention (TI) to reduce the consequences of the turnover. This study aims to examine the mediating role of employees’ JS between leaders’ emotional intelligence (EI), OC, and employees’ TI, with the employment of theory of reasoned action (TRA). A sample of 236 operational employees in five-star and four-star hotels in Jordan were selected by using stratified random sampling technique. Reliability test, data screening, factor analysis, correlation, multiple regression were executed to test the research hypotheses. Factor analysis exhibited one dimension of Leaders’ EI. OC produced two dimensions named as normative continuance commitment and affective commitment. Two factors renamed as intrinsic and organisation-based self-esteem (OBSE) for job satisfaction. TI divided for two dimensions renamed as thought to quit and behavioural loyalty. Results revealed that no significant effect between leaders’ EI, normative continuance commitment, and OBSE with thoughts of quitting. Normative continuance commitment, organization-based self-esteem, and intrinsic JS, influence positively on the behavioural loyalty. Whereas, this study has found only two mediating effects which are partially mediating effects of OBSE on normative continuance commitment and behavioural loyalty, and fully mediating effects of intrinsic JS on normative continuance commitment and behavioural loyalty. Through the application of TRA, TI can be explained as a negative response of employees to the unfulfilled obligation by organizations, as expected in an employee-employer relationship.